(untitled) (Eurasian Research Bulletin, 2022)
The article provides some recommendations on the importance of using modern pedagogical technologies in the field of wrestling, worldview and thinking, the formation of scale, the formation of physical, spiritual and moral qualities of the Department of Preschool Education and Pedagogy